STRATEGI CHINA DALAM MENGAMANKAN SUPLAI ENERGI DI KAWASAN AFRIKA TAHUN 2000-2010 - Ayu, Ajeng Puspita (Global and Policy Journal of International Relations, 2019)
This study analyzed the energy security strategies of China through increasing energy supply security in Africa from 2000-2010. It used qualitative methods by taking data through library studies. This study found that China uses investments (joint ventures and acquisitions) and infrastructure assistance as a strategy to achieve its energy security in Africa. During 2000-2010, China's energy production and consumption needed an imbalance that made China have to secure energy so that it could still be accessed with normal wheels. In implementing a strategy to achieve energy security, China is driven by a factor of a competitive advantage which must also be successful. China encourages its national oil companies to conduct energy exploration in Africa through investments (joint ventures and procurement) as well as providing infrastructure development assistance to countries with the largest oil reserves in Africa. Keywords: Energy Security, Comparative Advantage, Foreign Aid, FDI DOI : https://doi.org/10.33005/jgp.v7i01.1812